THE INNOVATIVE ELEMENTS IN NON-FORMAL EDUCATION OF INDONESIA: PERFECTIVE OF LEARNING OF ISLAMIC MANAGEMENT - Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2021)
To observe the development in the power of cognitive knowledge as learning of Islamic management for embodying Corruption free and excellence human resource for Indonesia. The article is reviewed about theoretical literature and research on cognitive knowledge to enhance the understanding of strategies for Islamic management that establish active roles for students, and conclude with consideration of the practical implications for embodying Corruption free and excellence human resource especially the student’s generation for Indonesia in 2045.